2014
DOI: 10.1177/0020872813515010
|View full text |Cite
|
Sign up to set email alerts
|

Who are the young people who are not in education, employment or training? An application of the risk factors to a rural area in the UK

Abstract: Young people who are not in education, employment or training (NEET) are a focus of government attention in the UK. For social service professionals the mechanisms underpinning the individual experience of NEET are critical to designing effective interventions. International comparisons point to similar experiences at the level of the individual family. This article examines the factors that may contribute to a young person becoming NEET and applies these to the demographics of a rural area in England. Poor ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 18 publications
1
50
0
4
Order By: Relevance
“…An important loss for people who live in the hinterland is the shutdown of public transportation as a consequence of systematic reductions in public funding (cf. Sadler, Akister, and Burch 2015). For the few young people in the hinterland, this is a serious loss; they depend heavily on transportation possibilities because the services that they need are now located far away.…”
Section: The Hinterland As the Edge Of The Learning Societymentioning
confidence: 99%
“…An important loss for people who live in the hinterland is the shutdown of public transportation as a consequence of systematic reductions in public funding (cf. Sadler, Akister, and Burch 2015). For the few young people in the hinterland, this is a serious loss; they depend heavily on transportation possibilities because the services that they need are now located far away.…”
Section: The Hinterland As the Edge Of The Learning Societymentioning
confidence: 99%
“…Factors which can be linked to poor educational attainment have been explored and include negative school experiences, lack of self-confidence and self-esteem, and persistent truancy (Furlong, 2006;Sachdev, Harries, & Roberts, 2006). The location of the study reported in this paper has high levels of NEET (Sadler, Akister, & Burch, 2014) and this is why the participating schools have proposed this research which explores the impact of summer activity projects, designed to promote an effective transition between primary and secondary school. The underpinning assumption of such projects is that a smooth transition will lead to greater pupil wellbeing, hence offering the potential for improved educational achievement.…”
Section: Poor Educational Achievementmentioning
confidence: 99%
“…Apart from the obvious problems for the young people, their families and schools at the time, these individuals are also at particular risk of becoming 'Not in Education, Employment, or Training' (NEET) when they reach age 16 (Bynner & Parsons, 2002). Sadler, Akister, and Burch (2014), for instance, found 40% of young people in England who had been permanently excluded from school were NEET for over 12 months, compared to just 6% of those who had not been excluded. The consequences of this can be detrimental to the health and well-being of the young people concerned, including increased risk of depression and mental health problems compared to older unemployed people (Public Health England, 2014), and having a higher risk of being involved in crime and drug use (Powis, Griffiths, Gossop, Lloyd, & Strang, 1998).…”
Section: Introductionmentioning
confidence: 99%